Laimaphelenchus persicus n. sp. (Nematoda: Aphelenchoididae) from Iran - Asghari, Ramazan; Pourjam, Ebrahim; Heydari, Ramin; Zhao, Zeng Qi (Zootaxa, 2012)
Laimaphelenchus persicus n. sp. is described and illustrated from the Caspian region of Iran, where it was extracted frombark collected from Pinus sylvestris. The new species is characterized by females with a body length of 615–925 µm, a(35.9–48.7), b (6.5–8.0), b’ (3.9–5.4), c (17.5–24.7), c’ (2.8–3.7), V (66.6–69.0%), stylet 10.0–11.5 µm, long post-vulvaluterine sac of 100–162μm, vulva having a flap, anteriorly sloping vagina massively sclerotized, and tail with an offsetterminus bearing 4 clearly pedunculate tubercles ending in 4–6 finger-like protrusions; and males with spicules 19–21μmlong, and three pairs of caudal papillae: one pre-anal, one at ca half tail length and one small pair anterior to tail terminus.The phylogenetic relationships of this new species were analysed using sequences of the D2/D3 region of the 28S ribo-somal RNA gene. SEM’s were prepared for morphologically informative parts and a dichotomous key to the genus Laimaphelenchus is given.